Preparation of black-titanium dioxide nanotubes by thermal decomposition of sodium borohydride - Murat Efgan Kibar (Journal of Advanced Research in Natural and Applied Sciences, 2021)
Titanium dioxide is a very attractive material in catalysis. Although the titanium dioxide exhibits superior proper-ties in ultra violet radiation, activity of the catalyst can be improved by some modifications specially for daylight radiation. Titanium dioxide was colored by thermal decomposition of sodium borohydride at 400 0C. The gray colored nanotube-titanium dioxide obtained where the molar ratio of titanium dioxide to sodium borohydride, 1.2 and 0.6. The black nanotube-titanium dioxide was prepared by making the ratio 0.3. While heterogeneous dispersion observed after coloring of commercial titanium dioxide, all photocatalysts prepared from nanotube-titanium dioxide were perfectly homogeneous after coloring. Structural properties of photocatalysts analysed by using XRD, BET and SEM. The nanotube form of titanium dioxide prepared by hydrothermal method. The nanotube photocatalysts are anatase and have high surface area. The activities of colored nanotubes investigated according to these structural properties. Photocatalysts could not be colored homogeneously with the hydrogen reduction process but efficient reduction and coloration obtained with sodium borohydride. The visible region activities of photocatalysts increased by coloring with sodium borohydride compared to coloring by hydrogen. While the surface structure is important, all prepared nanotube-titanium photocatalysts exhibited more efficient color removal yield with regard to commercial one. More active catalysts prepared for absorption of daylight energy and 98.4 % color removal yield from 30 ppm methylene blue solution obtained with black nanotube-titanium dioxide photocatalyst.